Analisis Implementasi Kebijakan Insentif Pajak Penghasilan Pasal 21 Ditanggung Pemerintah Dalam Rangka Pemulihan Ekonomi Pada KPP Pratama Jakarta Koja Tahun 2021 - Rosa Anjelita; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2022)
The research was motivated by the impact of the Covid-19 pandemic that first appeared in Indonesia in early 2020 on economic growth. To overcome the impact of the pandemic, the Indonesian government issued a government-borne article-21 income tax incentive policy to restore the situation for people affected by the pandemic. This study aims to analyze the implementation of the article-21 income tax incentive policy in an effort for economy recovery at the Primary Tax Office of Koja, Jakarta in 2021. The study was compiled using a qualitative descriptive method. Data sources consist of primary data, namely the results of interviews, and secondary data, namely documentation data. The results of the study show that the implementation of the government-borne article-21 income tax incentive policy at the Primary Tax Office of Koja, Jakarta in 2021 has begun in the post-covid-19 economic recovery stage. The result is that tax revenues continue to increase but the government continues to provide tax incentives. Only taxpayers who meet the criteria are entitled to take advantage of incentives. The campaign continues to be carried out through social media, but based on the results of interviews, there are several inhibiting factors, such as the delivery of the campaign which is not detailed enough, limiting tax withholding agent understanding, and the lack of readiness of tax officials. Efforts that need to be made are to optimize campaigns for tax withholding agent and improve the capacity of human resources in the tax office.